Laparoscopic nephrectomy in crossed fused kidney ectopia with severe hydronephrosis in 2 year-old child - Ghassan Nakib; Ziad Nesnas; Salvatore Amoroso; Valeria Calcaterra; Gloria Pelizzo (Elsevier, 2020)
Introduction: There are no specific recommendations for the surgical management of crossed fused renal ectopia (CFRE), but a laparoscopy has been proposed in a limited number of children. We report the case of a complex CFRE with severe hydronephrosis in a child treated by laparoscopic nephrectomy. Case report: A 2-year-old boy was admitted for hip and abdominal pain. A CFRE was diagnosed. Laparoscopic nephrectomy was suggested. The right crossed ectopic kidney appeared fused at its upper pole to the lower pole of the left kidney. The left kidney was in total rotation postero superiorly The left ureter crossing over the ectopic dilated right pelvis deliniated the fusion line between both kidneys. The right ureter was dissected distally. The right artery and vein were dissected and the right kidney pelvis opened making the separation of the kidneys easier and so reducing the danger of damaging the lower pole of the left kidney. During the dissection an aberrant vein arising from the left iliac vein and draining from both kidneys was identified. The right vein was dissected preserving the left vein, and the nephrectomy completed. Conclusions: Laparoscopy is a recommended option to treat CFRE, offering all advantages of this approach. Keywords: Laparoscopic, Nephrectomy, Crossed fused kidney ectopia, Child